The effect of oral contraceptives on cortisol metabolism - Burke, C. W. (1969)
The administration of oral contraceptives which contain oestrogen increases non-protein-bound plasma cortisol levels at 9 am as well as protein-bound and total cortisol levels. These increases are dependent on the dose of oestrogen; they are not usually seen with progestogen-only or `low-dose' oestrogen (0·05 mg mestranol or less) preparations. `Standard' oral contraceptives (0·1 mg mestranol or equivalent) produce some elevation of unbound cortisol levels at 9 am (from a normal mean of 0·66 μg/100 ml to 1·02 on the `pill') but this elevation is less than that associated with high-dose oestrogen treatment of, for example, prostate cancer (mean 1·8 μg/100 ml). Since unbound cortisol levels in plasma are controlled by a hypothalamic feedback mechanism, it appears that oral contraceptives have some effect on this mechanism. Possible long-term effects of oral contraceptives on hypothalamopituitary function require examination. However, the plasma unbound cortisol to which the tissues are exposed at 9 am does not measure the overall exposure of tissues to cortisol throughout the 24 hours. Neither does measurement of cortisol production rate or urinary metabolite excretion accurately reflect the exposure of tissues to cortisol during oestrogen treatment, because of the complex effects of oestrogen on hepatic metabolism of steroids, steroid-protein binding, and the increased size of the extracellular cortisol pool. The overall exposure of tissues to unbound cortisol is measured better by urinary free cortisol excretion. Urinary free cortisol excretion is a measure of the integrated area under the diurnal curve of plasma unbound cortisol, ie, of the 24-hour exposure of tissues to unbound cortisol. Urinary free cortisol excretion is normal in women taking low-dose oestrogen or progestogen-only contraceptives, and is only trivially increased by the standard `pill'. Thus increased exposure of tissues to unbound cortisol is likely to be only a minor factor in the metabolic responses to oral contraceptives. In contrast, urinary free cortisol excretion (mean normal 38 μg/24 hours) is increased by high-dose oestrogen administration for prostatic cancer (mean 110 μg/24 hours); this is because the diurnal rhythm of unbound cortisol is impaired. It is thus unwise to ascribe effects of oral contraceptives to increased exposure of tissues to cortisol, except in the liver where it is possible that the increased concentration of protein-bound cortisol they cause may exert metabolic effects. The preparations which cause least change in cortisol metabolism are the low-dose oestrogen or progestogen-only contraceptives.